Adsorption-Desorption Profile of Methylene Blue Dye on Raw and Acid Activated Kaolinite - Nurul Ain Safiqah Md Sandollah; Sheikh Ahmad Izaddin Sheikh Mohd Ghazali; Wan Nazihah Wan Ibrahim; Ruhaida Rusmin (Universitas Gadjah Mada, 2020)
The efficiencies of raw (RK) and acid activated (0.5 M AAK) kaolinite clay minerals to remove methylene blue (MB) dyes in aqueous solution were investigated and compared. The 0.5 M AAK was prepared by treatment of RK in dilute 0.5 M HCl aqueous solution under reflux. Kaolinite adsorbents were characterized and their MB removal performances were evaluated via the batch method. MB desorption from spent kaolinites was investigated at pH 4 to 8. The MB removal was increased with increasing initial dye concentration, agitation speed and adsorbent dosage in 60 min reaction time at pH 6. Both kaolinites showed high MB removal (up to 97%). The Freundlich model has the best-fit equilibrium adsorption isotherm model for RK and 0.5 M AAK. The kinetic data for both adsorbents showed strong agreement with the pseudo second order kinetic model (r2 > 0.98). Nevertheless, the spent RK adsorbent demonstrated a significant higher MB retention than 0.5 M AAK in desorption experiments. Kaolinite clays have great potential as cost-effective materials for dyes removal in wastewater treatment.